Isolated CA 19-9 elevation as preceding finding of colorectal carcinoma - Sahın, Abdurrahman; Bilgiç, Yılmaz; Cengiz, Mustafa; Altinsoy, Hasan Baki (My University, 2016)
Rectal bleeding, change in bowel habits, abdominal pain are cardinal symptoms of colorectal carcinoma. Otherwise, weight loss, fatigue and weakness do not suggest colorectal carcinoma. Carbohydrate antigen (CA) 19-9 level is higher in several malignancies, especially gastrointestinal malignancies, and some benign conditions. Herein, we present a patient who is referred to our clinic with the complaint of fatigue and significant CA 19-9 elevation, diagnosed as metastatic colorectal carcinoma. Presenting case highlights that CA 19-9 elevation might be the only finding of colorectal carcinoma in even patients with nonspecific complaints
Keywords: Genel ve Dahili Tıp; Patoloji; Onkoloji